2022
DOI: 10.1002/ldr.4387
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of ecological programs on land use and ecosystem services since the 1980s: A case‐study of a typical catchment on the Loess Plateau, China

Abstract: China' Loess Plateau, which was once dominated by sloping fields with poor farming conditions and serious soil erosion, has experienced a series of ecological programs. This article sought to explore the impacts of ecological programs on land use and ecosystem services in a typical catchment of China's Loess Plateau from 1984 to 2017, and thus understand what needs to be improved for future ecological programs. The findings showed that: (a) Due to the implementation of various ecological programs, the land use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…In addition, farmers could improve their livelihoods by obtaining farmland transfer funds, wages, and share proceeds. Overall, the agronomic technology based on the agricultural geographical engineering could activate farmland resources to optimize the spatial structure, industrial structure, organizational structure, and human‐environment interaction (Liu, 2020), thus helping to reduce the degradation risk of NCF and realize the synergy of socioeconomic development and ecological restoration in the LP's watershed (Lescourret et al, 2015; Liu & Li, 2017a; Li et al, 2022), which is helpful for farmland protection and rural revitalization (Liu et al, 2020) (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, farmers could improve their livelihoods by obtaining farmland transfer funds, wages, and share proceeds. Overall, the agronomic technology based on the agricultural geographical engineering could activate farmland resources to optimize the spatial structure, industrial structure, organizational structure, and human‐environment interaction (Liu, 2020), thus helping to reduce the degradation risk of NCF and realize the synergy of socioeconomic development and ecological restoration in the LP's watershed (Lescourret et al, 2015; Liu & Li, 2017a; Li et al, 2022), which is helpful for farmland protection and rural revitalization (Liu et al, 2020) (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, farmers continue their traditional crop planting with an extensive management mode after the GLCP, which exacerbates the degradation of NCF with higher sensitivity to tillage , 2017). Farmers as 'Homo economicus' usually abandon the NCF, which further renders farmland degradation over the years Li et al, 2022). In view of the above problems, this study proposed reconstructing soil microstructure to improve farmland quality and optimizing planting structure to boost agricultural profits according to the agricultural geographical engineering, and the effect was evaluated by the field experiment.…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…As the concept of ecosystem services (ESs) has attracted extensive attention, and an increasing number of scholars have suggested that ESs should be included in decision‐making and ecosystem management (Costanza et al, 1997; Frelichova et al, 2014). For instance, Li et al (2022) pointed out that ERPs in the Loess Plateau significantly improved ESs except food production. However, different scholars often use different indicators, thus making it difficult to compare their results.…”
Section: Introductionmentioning
confidence: 99%